Bow-Legs and Knock-Knees in Children - Self Resolving or Pathological Deformity - Shaikh Naeem-ul- Haq; Syed Abdur Rub Abidi; Abdul Rehman Khan; Salman Adil; Imran Samdani; Syed Adnan Ahmed (JLUMHS, 2019)
OBJECTIVE: To identify and differentiate the self-resolving Paediatric Orthopedic conditions namely bow-legs and knock-knees from pathological conditions like metabolic bone diseases - rickets and bone dysplasias. METHODOLOGY: This prospective descriptive, non-randomized, convenience sampling technique study was conducted in the out patient department of the Orthopedic units of the Jinnah Medical College Hospital Karachi, Dow University Hospital Ojha Campus Karachi and Fatima Hospital Baqai University Karachi from February 2012 - January 2018. Total three hundreds children between 1-8 years of age were included with deformities comprising mainly of bowlegs and knock-knees. We included the children having nutritional deficiencies alongside former deformities, and excluded children with neurological disturbances or other syndromes. A detailed history of each patient was taken, emphasizing their perinatal history and developmental milestones. RESULTS: Out of 300 patients 224 (74.67%) had improvement in deformity of legs without any active treatment. There were 64 (21.33%) children, who required treatment, were diagnosed as ricketic patients. There were another group of 12 (4%) children who didn’t show improvement without active intervention. They were categorized as suffering from epiphyseal dysplasias or post-traumatic epiphyseal injury. CONCLUSION: The majority of deformities like bowlegs and knock-knees in children are self-resolving and are considered as physiological variant of musculoskeletal development.The knowledge of spontaneous resolution saves both the time and money spent unnecessarily on these normal variants.